Identification and antioxidant activity of carotenoids from superfine powder of Rhodobacter sphaeroides - Li, Zuming; Kong, Lina; Hui, Bodi; Shang, Xiaoya; Gao, Liping; Luan, Na; Zhuang, Xuliang; Wang, Dong; Bai, Zhihui (Emirates Journal of Food and Agriculture, 2017)
The interest in carotenoids from the natural-antioxidant point of view has recently risen sharply because of their substantial health benefits. Here, we report the identification and antioxidant activity of carotenoids extracted by superfine grinding from Rhodobacter sphaeroides 3757 which is a species of photosynthetic bacteria. After separation and purification by silica gel column chromatography and reversed-phase high performance liquid chromatography (RP-HPLC), the four major carotenoids from the superfine powder of R. sphaeroide 3757 were identified as bixin, hydroxyspheroidenone, 3,3¢,4¢-tetrahydrospirilloxanthin-20-al, and spheroidenone by reversed phase - high performance liquid chromatography - atmospheric pressure chemical ionization - mass spectrometry (RP-HPLC-APCI-MS). The antioxidant activity of the carotenoids extracted after superfine grinding of dry biomass of R. sphaeroide 3757 was higher than that after ultrasonic treatment. When the ratio solvent-to-solid was 30, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging activity, reducing power, and lipid peroxidation inhibitory activity of the extracts after superfine grinding were 74.0% ± 3.1%, 0.497 ± 0.022, and 77.6% ± 3.2%, respectively. By contrast, the extracts after ultrasonic treatment, these numbers were 61.0% ± 2.5%, 0.328 ± 0.014, and 55.2% ± 2.3%, respectively. These results indicate that carotenoids from R. sphaeroide 3757 show a significant antioxidant activity in vitro in a concentration-dependent manner, and that superfine grinding is the optimal extraction method. We hope to provide scientific guidance for commercial production of natural- antioxidant and functional food from carotenoids of R. sphaeroide.